(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The peculiarities of the national-cultural environment play a key role in the formation of ecological culture among students of higher educational institutions of the Republic of Karakalpakstan. The study analyzes the interrelationship of Karakalpak national traditions, attitude towards nature, and ecological consciousness. The results show the positive influence of the national environment on the development of ecological culture.